HASIL BELAJAR KETERAMPILAN PROSES SISWA MELALUI IMPLEMENTASI MEDIA PEMBELAJARAN TEORI KINETIK GAS BERBASIS PENDEKATAN INKUIRI DI KELAS XI MIA 3 SMA NEGERI 4 PEKANBARU - Dea Fitriana; Zulhelmi Zulhelmi; Fakhruddin Z Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study is to the result of student’s process skill of class XI MIA 3 SMA Negeri 4 Pekanbaru on the material of kinetic theory of gas with the application of instructional media. This form of research is Pre Experimental Design with One Shot Case Study design. The subject of this research is class XI MIA 3 SMA Negeri 4 Pekanbaru. Instrument of the data collection was test of the learning result of students process skill given to subject of the research after giving treatment in the form of learning process based on inquiry approach. The data analysis technique used was descriptive analysis. Data analysis technique used is descriptive analysis. The results showed average absorption. It can be concluded that the implementation of instructional media of gas kinetic theory in the form of experimental device based on inquiry approach can improve the learning result of students' process skill on the material of gas kinetic theory in SMA Negeri 4 Pekanbaru.Keywords : The Result of Student’s Process Skill, Learning Media, Inquiry Approach